Identifying Effective Pedagogical Approaches for Online Workplace Training: A case study of the South African wood products manufacturing sector - Macdonald, Ian S.; Bullen, Mark; Kozak, Robert A. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
This study investigated appropriate pedagogical techniques for workplace e-learning programs in the South African wood products (furniture) manufacturing sector. The study found that learners responded favourably to constructivist teaching approaches, such as asynchronous discussions, open-ended task-based activities, and assignments incorporating authentic, real-world examples. Learners viewed constructivist activities to be more useful than quizzes and traditional essay-based assignments, as they allowed new concepts to be learned in context and were perceived to promote deeper understanding of the subject matter. Nevertheless, they valued the inclusion of a blend of pedagogical approaches in the course design, as this enabled them to approach and analyze new concepts in an assortment of ways. Learners placed importance on regular interaction with other learners and course instructors, and were strongly in favour of including face-to-face components in Web-based courses.